Intrinsic Expression of Immune Checkpoint Molecule TIGIT Could Help Tumor Growth in vivo by Suppressing the Function of NK and CD8+ T Cells - Zhou, Xiu-Man; Li, Wan-Qiong; Wu, Ya-Hong; Han, Lu; Cao, Xin-Guang; Yang, Xuan-Ming; Wang, Hong-Fei; Zhao, Wen-Shan; Zhai, Wen-Jie; Qi, Yuan-Ming; Gao, Yan-Feng (Frontiers in Immunology, 2018)
TIGIT, an immune checkpoint molecule widely expressed on NK cells, activated T cells and Tregs, has been involved in delivering inhibitory signals through the interaction with PVR. The blockade of TIGIT/PVR interaction is a promising approach in cancer immunotherapy. Here, we unexpectedly discovered the expression of TIGIT in murine tumor cells. To elucidate the mechanism of such intrinsic expression, TIGIT knockout murine colorectal CT26 cell line was generated by using CRISPR/Cas9 system. Although TIGIT knockout showed no effects on proliferation and colony formation of CT26 cells in vitro, the tumor growth in mice was considerably inhibited. TIGIT knockout led to the increase of IFN-γ secretion by NK and CD8+ T cells. Further, in BABL/c nude mice or CD8+ T cells depleting mice, the promotion of tumor growth was significantly diminished, suggesting that CD8+ T cells were involved in the tumor promoting process mediated by intrinsic TIGIT. In addition, blocking TIGIT/PVR interaction by the antibody or recombinant PVR protein could elicit anti-tumor effects by facilitating the tumor infiltration and restoring the function of CD8+ T cells. We therefore propose a novel TIGIT/PVR interaction mode that tumor intrinsic TIGIT delivers inhibitory signals to CD8+ T cells and NK cells by engaging with PVR.